PERAN KOMITMEN ORGANISASI SEBAGAI MEDIASI PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI LEMBAGA PEMASYARAKATAN KELAS IIA KENDARI - La Ode Abdul Faris; La Hatani La Hatani; Asrip Putera (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This research aimed to determine the direct and indirect influence of work discipline and organizational culture to the employees performance trough organizational commitment. The population in this research was 119 employees in Kendari class IIA Penitentiary with 25% samples from 119 calculate by Arikunto. The data was collected by distributing questionnaires derectly to the respondent. The technique of data analysis was Partial Least Square (PLS) 3.0                 The research result showed work discipline influenced positively and signifikanly toward organizational commitment and employee performance. Organizational culture directly influence but not significant to organizational commitment. Organizational culture have positive and signifikant influence to employee performance. Organizational commitment have positive and significant influence to employee performance. Organization commitment is able to mediate work discipline on employees performance. Organization commitment is not to mediate organizational culture on employees performance.